PENGEMBANGAN PENYUSUNAN INSTRUMEN FOUR-TIER DIAGNOSTIC TEST UNTUK MENGUNGKAP MISKONSEPSI MATERI SISTEM EKSKRESI DI SMA NEGERI 1 MAYONG JEPARA - Wilantika, Nurul; Khoiri, Nur; Hidayat, Saifullah (Sains and Technology Faculty, Walisongo State Islamic University, 2018)
This study aims to develop and describe feasibility a Four-tier diagnostic test instrument to figure out students' misconceptions in the material of the Excretion System.This study aims to develop a Four-tier diagnostic test instrument to figure out students' misconceptions in the material of the Excretion System. The type of this study is R & D (Research and Development) from Sugiyono (2017) with 10 stages. Those 10 stages are identification of potential and problems, data collection, product design, product validation, design revisions, product trials, product revisions, usage trials, product revisions and mass production. The trial subjects were students of class XII MIPA 3 (Test instrument), class XI MIPA 2 (product trial) and class XI MIPA 1 and class XI MIPA 4 (trial use) SMA Negeri 1 Mayong Jepara. This study used observation, documentation, questionnaire, interview and test as research method. First finding, the Four-Tier Diagnostic Test consists of four levels; the question, the level of answer confidence, reason and level of reasoning confidence. The instruments produced include grids, work instructions, test questions, answer keys, answer sheets, scoring guidelines and results interpretation guidelines. Second finding, the results showed that the Four-tier diagnostic test instrument was feasible to be used to reveal student misconceptions. Validity testing by 9 validators shows that the instrument developed is valid. Test validity shows 7 valid category questions, 16 invalid category questions. Test reliability developed by 0.699 means that the problem is reliable. Characteristics of the questions developed were (1) Difficulty level (2 difficult questions, 10 moderate questions, 8 easy questions and 3 very easy questions), (2) Different Power (2 good questions, 17 enough questions and 4 bad questions), and ( 3) Foolers can function properly. There are 41 misconceptions from 13 sub-topics developed.